O estresse dos enfermeiros no âmbito hospitalar - Rosa, Carolina Leite da (Universidade do Vale do Rio dos Sinos, 2012)
The survey aimed to ascertain, based on the scale of stress, which Bianchi domain more stressful to a group of nurses in a hospital in the metropolitan region of Porto Alegre, identifying the most relevant activities as being shifted to the stress. The data were collected by means of questionnaires. The population was sure 20 nurses with female predominance (85%) and an average age of 30 to 40 years (50%). A little less than half of the nurses studied graduate (45%). Graduation time is in the range of 2 to 5 years (75%), while the length of service was on average of 55% for 1 year of profession. The results indicated that nurses have medium level of stress, and that areas F-working conditions for the performance of activities of nurses, and C-activities related to personnel administration, were judged to be the most stressful for individuals searched. Notes that for the nurse, despite his ready and effective action against the patient care, working conditions and staff supervision are more stressful.
Keywords: Estresse; Enfermagem; Saúde ocupacional; Stress; Nursing; Occupational health